PEMATAHAN DORMANSI BIJI KENERAK (GONIOTHALAMUS UMBROSUS) MENGGUNAKAN HORMON 2,4-D DAN BAP SECARA MIKROPRAPAGASI - Imam Mahadi (Jurnal Sagu, 2011)
Kenerak (Goniothalamus umbrosus) is one species of Goniothalamus genus and becomes sourcesof important traditional medicines for local people in Southeast Asia. Goniotltalamus plants are consideredto have great sources of pharmaceuthical substances and used as anticancer agent. Based on this thepreliminary study was carried out to overcome dormancy of kenerak seeds using seed explants showed thatbest result to enhance rapid germination was found for M S A4 (0.5 mg/12.4-D) medium after 3-8 weeksculture and total germination on E6 (2.0 mg/l 2.4-D 4- 0.5 mg/l B A P ) medium of 80%. This is better thanconventional methods which is about 6-12 months. Therefore la vitro technique can be used to overcomedormancy in seeds of kenerak.